2019
DOI: 10.3847/1538-4357/ab4128
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Cycle Period and Parity of Stellar Magnetic Activity with Dynamo Modeling

Abstract: Observations of chromospheric and coronal emissions from various solar-type stars show that the stellar magnetic activity varies with the rotation rates of the stars. The faster the star rotates, its magnetic activity gets stronger but activity cycle period does not show a straightforward variation with the rotation rate. For slowly rotating stars, the cycle period decreases with the increase of rotation rate, while for the fast rotators dependency of cycle period on rotation is presently quite complicated. We… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 91 publications
1
9
0
Order By: Relevance
“…In the solar-like DR branch, we find the magnetic field strength increases with the decrease of rotation period. This result is, in general, agreement with the observational findings (Noyes et al 1984a;Petit et al 2008;Wright et al 2011;Wright & Drake 2016), the global MHD convection simulations (Viviani et al 2018;Warnecke 2018), and mean-field dynamo modellings (Jouve et al 2010;Karak et al 2014a;Kitchatinov & Olemskoy 2015;Hazra et al 2019). However, our model does not produce the observed saturation of magnetic field in the very rapidly rotating stars, which in the kinematic models, requires some additional dynamo saturation (Karak et al 2014a;Kitchatinov & Olemskoy 2015).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In the solar-like DR branch, we find the magnetic field strength increases with the decrease of rotation period. This result is, in general, agreement with the observational findings (Noyes et al 1984a;Petit et al 2008;Wright et al 2011;Wright & Drake 2016), the global MHD convection simulations (Viviani et al 2018;Warnecke 2018), and mean-field dynamo modellings (Jouve et al 2010;Karak et al 2014a;Kitchatinov & Olemskoy 2015;Hazra et al 2019). However, our model does not produce the observed saturation of magnetic field in the very rapidly rotating stars, which in the kinematic models, requires some additional dynamo saturation (Karak et al 2014a;Kitchatinov & Olemskoy 2015).…”
Section: Resultssupporting
confidence: 91%
“…As the meridional flow transports the magnetic fields from source regions, the cycle duration tends to be longer with the decrease of meridional flow (Dikpati & Charbonneau 1999;Karak 2010). This was usually seen in previous flux transport dynamo models of stellar cycles (Nandy 2004;Jouve et al 2010;Karak et al 2014a), but not in the turbulent pumping-dominated regime (Karak & Cameron 2016;Hazra et al 2019). Therefore, in Set C in which meridional circulation is decreased with the rotation rate following Equation ( 12), we expected an increase of cycle period.…”
Section: Stellar Dynamo With Solar and Anti-solar Drmentioning
confidence: 55%
“…As we pointed out in §3.4, theoretical considerations suggest that faster rotating stars have weaker meridional circulation, which would lead to longer cycle periods [112,62]. Hazra et al [113] have suggested that the inclusion of the downward turbulent pumping may help in closing the gap between observations and theory.…”
Section: The Flux Transport Dynamo Modelmentioning
confidence: 83%
“…Magnetic field is a ubiquitous property of stars and many of them show a cyclic magnetic activity. The underlying dynamo mechanism i.e., the non-linear interaction between velocity field and magnetic field in the convection zone, drives the cyclic magnetic activity in stars (Parker 1955;Choudhuri et al 1995;Charbonneau 2014;Hazra et al 2014Hazra et al , 2017Hazra et al , 2019. The CaII H&K project of the Mount Wilson Observatory (Wilson 1978;Noyes et al 1984;Baliunas et al 1995) has monitored chromospheric activity of 111 stars of spectral types F2-M2 on or near the main sequence, and found that Sun-like cyclic activity is common and exhibited by many cool dwarfs.…”
Section: Relationship Between Magnetic Cycle and Xuv Radiationmentioning
confidence: 99%
“…Temporal variation was also observed in the Hα transit of HD189733b (Barnes et al 2016), confirming once more that evaporating atmospheres undergo temporal evolution. One likely explanation is that these temporal changes are caused by stellar variability, i.e., time-variations in the properties of host stars, which can take place in the form of, e.g., cyclic magnetic activity, strong flares or variation in stellar winds or total stellar output radiation (e.g., Baliunas et al 1995;Tokumaru et al 2010;Boro Saikia et al 2018;Hazra et al 2019).…”
Section: Introductionmentioning
confidence: 99%